Embryonic frog epidermis: a model for the study of cell-cell interactions in the development of mucociliary disease - Eamon Dubaissi; Nancy Papalopulu (The Company of Biologists, 2011)
SUMMARY Specialised epithelia such as mucociliary, secretory and transporting epithelia line all major organs, including the lung, gut and kidney. Malfunction of these epithelia is associated with many human diseases. The frog embryonic epidermis possesses mucus-secreting and multiciliated cells, and has served as an excellent model system for the biogenesis of cilia. However, ionic regulation is important for the function of all specialised epithelia and it is not clear how this is achieved in the embryonic frog epidermis. Here, we show that a third cell type develops alongside ciliated and mucus-secreting cells in the tadpole skin. These cells express high levels of ion channels and transporters; therefore, we suggest that they are analogous to ionocytes found in transporting epithelia such as the mammalian kidney. We show that frog ionocytes express the transcription factor foxi1e, which is required for the development of these cells. Depletion of ionocytes by foxi1e knockdown has detrimental effects on the development of multiciliated cells, which show fewer and aberrantly beating cilia. These results reveal a newly identified role for ionocytes and suggest that the frog embryonic skin is a model system that is particularly suited to studying the interactions of different cell types in mucociliary, as well as in secretory and transporting, epithelia.